Road Safety Management in Brazilian Logistics Companies: An Empirical Study of Practices, Motivators, and Barriers - Delmonico, Diego Valerio Godoy [UNESP]; Delgado, Fernanda C. M. [UNESP]; Bezerra, Barbara Stolte [UNESP] (MDPI, 2025)
This study explores how Brazilian logistics companies manage road safety by identifying key practices, motivators, and barriers. While traffic safety has been widely studied, few investigations adopt an organizational perspective, especially in the logistics sector. Addressing this gap, we applied a mixed-methods approach combining expert input (qualitative phase) and a structured survey of industry professionals (quantitative phases). The findings reveal that practices such as infrastructure development, driver training, and compliance monitoring are perceived as most effective. Motivators include operational planning and economic incentives, while major barriers involve lack of internal motivation, awareness, and resource constraints. Factor analysis confirmed the structure of practices, motivators, and barriers, while a SWOT framework provided strategic insights into internal strengths and external challenges. This study offers practical recommendations for integrating safety into strategic planning, improving training, and strengthening collaboration with public actors. By aligning safety efforts with long-term business goals, logistics providers can enhance both operational performance and social responsibility. These results contribute to global discussions on sustainable logistics by supporting key Sustainable Development Goals, including SDG 3.6 (road safety), SDG 8.8 (safe working environments), SDG 9.1 (sustainable infrastructure), and SDG 11.2 (safe and accessible transport).